2001
DOI: 10.1074/jbc.m007405200
|View full text |Cite
|
Sign up to set email alerts
|

A Rice Functional Transcriptional Activator, RISBZ1, Responsible for Endosperm-specific Expression of Storage Protein Genes through GCN4 Motif

Abstract: The GCN4 motif, a cis-element that is highly conserved in the promoters of cereal seed storage protein genes, plays a central role in controlling endospermspecific expression. This motif is the recognition site for a basic leucine zipper transcriptional factor that belongs to the group of maize Opaque-2 (O2)-like proteins. Five different basic leucine zipper cDNA clones, designated RISBZ1-5, have been isolated from a rice seed cDNA library. The predicted gene products can be divided into two groups based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 51 publications
4
149
0
Order By: Relevance
“…It is believed that their temporal and spatial specificities are conferred by endosperm-specific TFs (VicenteCarbajosa et al, 1997). The discovery of genes homologous to O2 and PBF in other cereal species supports this empirical hypothesis (Albani et al, 1997;Conlan et al, 1999;Oñate et al, 1999;Onodera et al, 2001;Mena et al, 2002;Yamamoto et al, 2006;Kawakatsu et al, 2009). However, in dicots, the seed specificity of storage protein gene expression is not necessarily regulated by seed-specific TFs.…”
Section: Endosperm-specific and Nonspecific Tfs Regulate Seed Storagesupporting
confidence: 58%
“…It is believed that their temporal and spatial specificities are conferred by endosperm-specific TFs (VicenteCarbajosa et al, 1997). The discovery of genes homologous to O2 and PBF in other cereal species supports this empirical hypothesis (Albani et al, 1997;Conlan et al, 1999;Oñate et al, 1999;Onodera et al, 2001;Mena et al, 2002;Yamamoto et al, 2006;Kawakatsu et al, 2009). However, in dicots, the seed specificity of storage protein gene expression is not necessarily regulated by seed-specific TFs.…”
Section: Endosperm-specific and Nonspecific Tfs Regulate Seed Storagesupporting
confidence: 58%
“…Amino acid substitutions in spG-GFP-AB(C78S), spG-GFP-AB(C79S), spG-GFP-AB(L82F), and spG-GFP-ABC(C79F) were introduced by PCR with mutagenic primers. The GFP fusion constructs were transferred into a binary vector derived from p8C-Hm (Onodera et al, 2001) containing the a-globulin promoter described previously (Wu et al, 1998) and the hygromycin phosphotransferase gene. Rice transformation was conducted as described previously (Goto et al, 1999).…”
Section: Gene Construction and Rice Transformationmentioning
confidence: 99%
“…Sequence analysis showed that some important cis-acting elements related to the endosperm expression were found in PDULL1-4, including the GCN4_motif and AACA motif (Figure 1). The GCN4 motif, a ciselement is highly conserved in the promoters of cereal seed storage protein genes and plays a central role in controlling endosperm-specific expression (Onodera et al, 2001). Multimers of the rice glutelin GCN4 motif can direct endosperm-specific expression in stable transgenic rice.…”
Section: Discussionmentioning
confidence: 99%